Pengaruh Bakteri Endofit Padi terhadap Penyakit Busuk Bulir Bakteri dan Pertumbuhan Tanaman Padi: Effects of Rice Endophytic Bacteria on Bacterial Grain Rot Disease and Rice Growth - Rahmadhani, Nahrisa; Munif, Abdul; Nawangsih, Abdjad Asih (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2025)
Effects of Rice Endophytic Bacteria on Bacterial Grain Rot Disease and Rice Growth Bacterial grain rot disease, caused by Burkholderia glumae, is an important disease that can reduce rice yields and is a seed-borne disease. Biological control through biopriming using endophytic bacteria is an alternative disease control method that has been widely used in various crops. This study aimed to assess the potential of endophytic bacteria from six rice varieties using biopriming techniques in controlling B. glumae and their ability to stimulate rice growth. The research stages consisted of isolation and biosafety testing of endophytic bacteria with potential as biological agents, in vitro antagonism assay against B. glumae using the cross streak method, phytotoxicity assay of endophytic bacteria on rice seeds, selection of potential bacteria using the analytical hyphenation process (AHP) method, and examining the ability of biopriming to control B. glumae and its effect on rice vegetative growth. A total of 133 endophytic bacterial isolates were successfully isolated from six rice varieties, and 27 isolates met the biosafety test requirements. In vitro and in vivo assay showed that eight isolates exhibited antagonistic activity against B. glumae, and 25 isolates increased rice seed germination. Three isolates were selected based on AHP results, i.e. BBZN3, BBAR4, and AKPAT4. Of these three isolates, AKPAT4 was the best at increasing the vigor index and germination level of rice seeds, as well as suppressing disease incidence and severity.